Henrik Ibsen, Emperor Julian, and the crisis of faith in modernity. (20th March 2023) - Boswell, Brad; Crawford, Matthew R; Stavrakopoulou, Anna
Abstract: Although it is one of his lesser known and performed plays, Henrik Ibsen considered Emperor and Galilean to be his Hovedverk—his 'main' or 'pivotal' work—in which he finally presented his positive worldview. It remains comparatively little studied in scholarship, though one scholar has recently argued that it is the key to unlocking his entire corpus. The present study builds upon past scholarship uncovering the works Ibsen drew upon in writing the play but goes beyond the mere question of its historical sources and accuracy to consider Ibsen's purpose for including the specific and precise pieces of historical texture he chose in the particular order and configuration he devised. In short, we aim to identify the creative purposes for his curating of the historical details he took from his sources. What emerges from our analysis is that, even when Ibsen is following the sources, his protagonist stands out as a strikingly modern figure, more at home in the nineteenth century than the fourth. Ibsen portrays his Julian struggling with doubt and uncertainty of a distinctly modern caste; he puts in his mouth criticisms of Christianity that stem from modernity rather than the historical figure; and he suggests that, just as Christianity had to prove victorious over paganism in late antiquity, so Christianity itself must be superseded in the modern era, though perhaps some aspects of it are worth preserving in the yet-to-arrive third empire.